Représentations de la forêt et répercussions sur la gestion des ressources forestières au Sénégal - Mamadou Diop (Éditions en environnement VertigO, 2012)
In Africa, programs targeting the management of natural forest resources often struggle to be successful. Most of those who conceptualize those programs usually only focus on the functionality and necessity of a reasonable use of its resources. They often neglect symbolic dimensions which nonetheless influence the relationship between the residents and the natural environment. Consequently, this article seeks to understand the representations that residents have of the Classified Forest of Patako as well as the possible consequences on the management of its resources. The collected data have revealed that for 23.5 % of interviewed residents, the forest is merely a bush. For 23 %, it represents a State good. 20.7 % perceive it as farming ground taken from the village land and only 13.4 % of residents believe that the classified forest is woodland belonging to bordering villages. The classified forest is also represented in the interview transcripts as foreb buur (State forest), foreb ñépp (everyone’s forest) or as xeewëlu Yàlla (divine gift). With respect to ownership of resources from the classified forest, 61.8 % of residents believe that the resources belong to the state, and only 16.6 % believe that they belong to local residents. These representations have engendered attitudes that are difficulty compatible with an integrated management of natural resources in that they suggest a weakening of ownership of the forest by the residents.